2019
DOI: 10.2139/ssrn.3337770
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Agent Methodology to Assess the Effectiveness of Alternative Systemic Risk Adjusted Capital Requirements

Abstract: We propose a multi-agent approach to compare the eectiveness of macroprudential capital requirements, where banks are embedded in an articial macroeconomy. Capital requirements are derived from alternative systemic-risk metrics that reect both the vulnerability or impact of nancial institutions. Our objective is to explore how systemic-risk measures could be translated in capital requirements and test them in a comprehensive framework. Based on our counterfactual scenarios, we nd that macro-prudential capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…(2016) found that contagion effects are most significant if the originating defaulted bank is highly leveraged. Accordingly, Gurgone and Iori (2019) focused on macro‐prudential capital requirements, and by testing several simulation scenarios, they showed how capital requirements could mitigate systemic risk. In this regard, Gaffeo et al.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2016) found that contagion effects are most significant if the originating defaulted bank is highly leveraged. Accordingly, Gurgone and Iori (2019) focused on macro‐prudential capital requirements, and by testing several simulation scenarios, they showed how capital requirements could mitigate systemic risk. In this regard, Gaffeo et al.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 99%
“…Similarly, Yao et al (2016) found that contagion effects are most significant if the originating defaulted bank is highly leveraged. Accordingly, Gurgone and Iori (2019) focused on macro-prudential capital requirements, and by testing several simulation scenarios, they showed how capital requirements could mitigate systemic risk. In this regard, Gaffeo et al (2019) and Leventides et al (2019), like other researchers, identified an inverse relationship between the capitalization level imposed on banks and financial contagion.…”
Section: Capital Requirementmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach to reduce the complexity of a system with such specifications could be to use a self-organizing multi-agent system [20]. In recent years, much partial research has been conducted using agent-based simulation on various concerns of IMM, i.e., systemic risk [19,[21][22][23][24], stability [21,25], market structure [21,26], trust [27], and default [19,28]. To the best of our knowledge, except for a few studies on interbank payment and settlement systems [29][30][31], a serious complete work may rarely be found on designing an agent-based architecture that can cover all the IMM functions and help to make decisions.…”
Section: Mas Applications In Immmentioning
confidence: 99%